Effect of dicationic ionic liquids on lyotropic liquid crystals formed by a binary system composed of Triton-X 100 and water - Thieghi, Leila T.; Longo Jr, Luiz S.; Licence, Peter; Alves, Sarah (Taylor & Francis, 2018)
In this work, binary mixtures of a non-ionic surfactant (Triton X-100) and water were studied with concentrations of 30%wt H2O, showing, lamellar mesophase at temperatures below 10oC. Different dicationic ionic liquids were used for doping these mesophases: 1,n-bis(3-methylimidazolium-1-yl)alkane, 1,n-bis(1-methylpyrrolidinium-1-yl)alkane and 1,n-bis(pyridinium-N-yl)alkane dibromide, where n = 6 and 8. Polarized Optical Microscopy and Small-Angle X-ray Scattering were used for identifying the mesophases and the influence of different dicationic ionic liquids on the lyotropic liquid crystals phase transitions. The addition of dicationic ionic liquids to the lyotropic liquid crystals samples led to changes in transition temperature and in mesophase structure itself (such as characteristic distances).